DOP38 Upadacitinib Therapy Reduces Crohn's Disease Symptoms Within the First Week of Induction Therapy. (30th January 2023) - Colombel, J F; Hisamatsu, T; Bresso, F; Thin, L; Parra, R; Ford, S; Remple, V; Lacerda, A P; Hecht, P; Mallick, M; Garrison, A; Regueiro, M
Abstract: Background: Upadacitinib (UPA), an oral, selective JAK inhibitor demonstrated superior efficacy for clinical remission compared with placebo (PBO) and an acceptable safety profile in patients with moderately to severely active Crohn's disease (CD) in 2 phase 3 induction trials, U-EXCEL (NCT03345849) and U-EXCEED (NCT03345836). 1-2 There remains an unmet need for therapies that provide rapid symptom relief in ambulatory patients with moderate to severe CD experiencing disease flares. This sub-analysis evaluated the efficacy of UPA 45 mg once daily (UPA45) on early symptomatic improvement for the first 15 days of treatment, using pooled data from U-EXCEL and U-EXCEED. Methods: U-EXCEL and U-EXCEED were multicentre, double-blind, PBO-controlled trials that enrolled patients who had average daily very soft or liquid stool frequency (SF) ≥4 and/or abdominal pain score (APS) ≥2 at baseline, plus a Simple Endoscopic Score for CD ≥6 (≥ 4 for patients with isolated ileal disease), excluding the narrowing component. Patients (n=1021) were randomized (2:1 ratio) to receive UPA45 (n=674) or PBO (n=347) for 12 weeks. First dose of study drug was administered on day 1. Improvement in daily symptoms of SF and APS, in addition to time to first achievement of daily SF/APS clinical remission were assessed. Results: Patients treated with UPA45 experienced a significant improvement in daily symptoms compared with PBO-treated patients, simultaneously achieving SF < 3 and APS ≤ 1 beginning at day 3 (9.6% UPA vs. 5.8% PBO) (P≤0.05, Figure 1A). Difference from PBO was maintained through day 15 (P≤0.05), except for day 4 (P=0.0518). Similar results were found when evaluating each symptom separately, with a higher proportion of patients who received UPA45 achieving either SF < 3, beginning at day 5 (31.6% UPA vs. 23.1% PBO, Figure 1B). UPA-treat patients attained significance for APS ≤ 1 beginning at day 6 (49.1% UPA vs. 39.3% PBO, Figure 1C), compared with patients that received PBO. Differences from PBO were sustained through day 15 for either symptom (P≤0.01 for both endpoints). A greater proportion of patients receiving UPA45 also demonstrated at least a 60% decrease in SF by day 5, compared to PBO, which was maintained through day 15 (P≤0.01, Figure 1D). Patients treated with UPA45 achieved daily SF/APS clinical remission significantly earlier than PBO-treated patients (median time to clinical remission: 13 days UPA45 vs 32 days PBO; P<0.0001, Figure 2). Conclusion: Patients who received UPA 45 mg once daily significantly improved daily symptoms of diarrhea or abdominal pain within the first week of treatment and achieved daily clinical remission faster than PBO-treated patients, providing rapid symptom relief.